Research Practice of Participatory Skills to Interpret The Principles of Buddhism and The Art of Young Contemporary Thailand with The Format of The Art Competitions - Thanatip Thipwaree (Faculty Of Arts and Design Sebelas Maret University, 2024)
Abstract This article is part of The Research Practice of Participatory Skills to Interpret The Principles of Buddhism and The Art of Young Contemporary Thailand with The Format of The Art Competitions. The objective is to enable students and young people to apply the philosophy, concepts, teachings, beliefs and attitudes of Buddhism to create works of art. Through organizing a contest and exhibiting works of art in the name